2022
DOI: 10.1108/ijoa-09-2020-2433
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the antecedents of employee engagement

Abstract: Purpose The purpose of this study is to investigate the relationship between employee engagement and general management, performance management, reward management and transformational leadership. Design/methodology/approach A survey was distributed to a mid-sized energy company based in North America. A two-stage hierarchical multiple regression was performed. Employee engagement was the dependent variable, and the control variables of age and education were entered at stage one. In stage two, the four varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Other studies found a positive relationship between leadership and employee engagement (Carasco-Saul et al , 2015). Leadership styles that were associated with improving employee engagement include transformational (Alam et al , 2022), authentic, charismatic, ethical (Bailey et al , 2015) and servant leadership (Lee et al , 2017). Additionally, previous studies identified the role of manager self-efficacy (Wollard and Shuck, 2011), supervisory coaching and leader empowering behavior in improving employee engagement (Bailey et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies found a positive relationship between leadership and employee engagement (Carasco-Saul et al , 2015). Leadership styles that were associated with improving employee engagement include transformational (Alam et al , 2022), authentic, charismatic, ethical (Bailey et al , 2015) and servant leadership (Lee et al , 2017). Additionally, previous studies identified the role of manager self-efficacy (Wollard and Shuck, 2011), supervisory coaching and leader empowering behavior in improving employee engagement (Bailey et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the organizational level, research shows that factors such as HRD positively influence employee engagement. For example, HRD practices that can boost employee engagement include opportunities for training and development (Lee et al , 2017), talent management (Wollard and Shuck, 2011), rewards and recognition (Basbous and Malkawi, 2017; Kossyva et al , 2022), coaching (Lyons and Bandura, 2021) and performance management (Alam et al , 2022). Also, existing literature supported other factors such as a climate of psychological safety (Bailey et al , 2015), team and coworkers support (Lee et al , 2017) and connection to mission and values (Akingbola and van den Berg, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examine five different correlates of WE. First, we examine sex, age, and education, as many other studies have found a relationship (Alam et al, 2022; Banihani et al, 2013). We predict that older people would express more WE (H1) because age is usually correlated with organizational rank, which is always correlated with job satisfaction (Oshagbemi, 1997).…”
Section: Work Engagementmentioning
confidence: 99%
“…Then, as a result of improved employee performance, organisational performance improves (Wijayati et al, 2022). The top two predictors of employee engagement are remuneration and performance management (Alam et al, 2022). Employee engagement leads to increased productivity and profit for the company (Chanana, 2021).…”
Section: Employee Engagementmentioning
confidence: 99%